(untitled) (Syracuse, N.Y, 2008)
Bringing the rich terrain of Arab American histories to bear on conceptualizations of race in the U.S., this groundbreaking volume fills a critical gap in the field of ethnic studies. Unlike most immigrant communities who either have been consistently marked as non-white, or have made a transition from non-white to white, Arab Americans historically have been rendered white and have increasingly come to be seen as non-white. matters to the study of Arab American histories and asks essential questions.
Keywords: Arab Americans,Người Mỹ gốc Ả Rập; Điều kiện xã hội; Social conditions,Thế kỷ 21